2012
DOI: 10.1158/1078-0432.ccr-11-3265
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of EGFR and KRAS Mutations in 3,026 Lung Adenocarcinomas: Higher Susceptibility of Women to Smoking-Related KRAS-Mutant Cancers

Abstract: Purpose The molecular epidemiology of most EGFR and KRAS mutations in lung cancer remains unclear. Experimental Design We genotyped 3026 lung adenocarcinomas for the major EGFR (exon 19 deletions and L858R) and KRAS (G12, G13) mutations and examined correlations with demographic, clinical and smoking history data. Results EGFR mutations were found in 43% of never smokers (NS) and in 11% of smokers. KRAS mutations occurred in 34% of smokers and in 6% of NS. In patients with smoking histories up to 10 pack-y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
424
8
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 556 publications
(492 citation statements)
references
References 50 publications
44
424
8
2
Order By: Relevance
“…While KRAS mutations were associated with a smoking history greater than 20 pack-years, the tumors resected from almost 10% of patients with smoking histories of 10 pack-years or less had KRAS mutations. DOGAN et al (42) 241 of 2,198); KRAS mutations were found in 34% of former or current smokers (627 of 1,860) and 6% (43 of 669) of never-smokers. EGFR mutations among smokers were most common for those with less than a 10 pack-year smoking history.…”
Section: Driver Mutationsmentioning
confidence: 96%
See 4 more Smart Citations
“…While KRAS mutations were associated with a smoking history greater than 20 pack-years, the tumors resected from almost 10% of patients with smoking histories of 10 pack-years or less had KRAS mutations. DOGAN et al (42) 241 of 2,198); KRAS mutations were found in 34% of former or current smokers (627 of 1,860) and 6% (43 of 669) of never-smokers. EGFR mutations among smokers were most common for those with less than a 10 pack-year smoking history.…”
Section: Driver Mutationsmentioning
confidence: 96%
“…A typical tumor contains two to eight driver mutations that can affect as many as 12 key cellular signaling pathways. Reported genetic alterations for lung adenocarcinoma include: EGFR (32,(42)(43)(44)(45)(46)(47), KRAS (42,(48)(49)(50)(51)(52), BRAF (53)(54)(55)(56), and ERBB2 (formerly HER2) (45, 56-60) driver mutations; ROS1 (32,(61)(62)(63), KIF5b-RET (32,64,65), and EML4-ALK rearrangements (20,45,57,61,(66)(67)(68)(69)(70); and other gene amplifications (20). An estimated 50% of lung adenocarcinomas in patients in Western populations have either an EGFR or KRAS driver mutation (42).…”
Section: Clinical Issuesmentioning
confidence: 99%
See 3 more Smart Citations